A combined XFEM and RSM approach for predicting crack propagation in nearby buildings during foundation pit construction - Wu, Zhaofeng; Wang, Tiancheng; Kuang, Yan; Zhu, Zhiliang; Xiao, Fenglong; Yang, Pengliang (Frontiers in Built Environment, 2025)
This paper addresses the issue of crack expansion in adjacent buildings caused by foundation pit construction and develops a predictive model using the response surface method. Nine factors, including the distance between the foundation pit and the building, soil elastic modulus, and density, were selected as independent variables, with the crack propagation area as the dependent variable. An orthogonal test of 32 conditions was conducted, and crack propagation was analyzed using the FEM-XFEM model. Results indicate that soil elastic modulus, Poisson’s ratio, and distance between the pit and building significantly impact crack propagation. A predictive model was developed through ridge regression and validated with additional test conditions. Single-factor analysis showed that elastic modulus and Poisson’s ratio of the silty clay layer, elastic modulus of sandy soil, and pit distance have near-linear effects on crack propagation. In contrast, cohesion, density, and Poisson’s ratio of sandy soil exhibited extremum points, with certain factors showing high sensitivity in specific ranges. This study provides theoretical guidance for mitigating crack propagation in adjacent buildings during excavation.